NGHIÊN CỨU TÍNH CHẤT VÀ CẤU TRÚC CỦA VẬT LIỆU COMPOZIT POLYETYLEN/PE-g-AM/CaCO3 - Hoàng, Thái; Đức, Vũ Minh; Giang, Nguyễn Vũ; Thẩm, Đỗ Quang (Vietnam Journal of Chemistry, 2012)
The composites of PE/CaCO3 with and without PE-g-AM compatibilizer were prepared by melt mixing in a Haake Rheomix 600p. The Haake torque (could be called as the relative melt viscosity) of the composites was recorded while mixing by Polylab V 4.1 software. The mechanical properties of the composites were tested by a WMP instrument, dielectric properties were measured by using a TR-10C dielectric loss measuring set and volume resistivity was measured by IV method using a TR-8401 DC instrument with applied voltage of 1000 V. The mophological structrure of the composites was studied by scanning electron microscopy (SEM). The results showed that CaCO3 and PE-g-AM increased relative melt viscosity of the composites, this proved that PE-g-AM enhanced the adhesion between CaCO3 and PE matrix while melt mixing them. The mechanical properties of the PE/CaCO3 composites strongly decreased with increasing CaCO3 contents. But by adding PE-g-AM, the mechanical properties of the PE/CaCO3 composites were improved significantly, especially in tensile strength. PE/CaCO3 and PE/PE-g-AM/CaCO3 composites had good electrical insulation properties, such as high resistivity and very low dielectric loss. The PE-g-AM compatibilizer played an important role for the enhancement of dispersity of CaCO3 in PE matrix, reducing agglomeration of CaCO3 particles in PE matrix.